Pelaku Pedofilia: Hukum Positif Atas Kasus Kekerasan Seksual - Priskilla Velicia Ong; Ariawan Gunadi (Universitas Widya Gama Malang, 2023)
Cases of pedophilia crimes are widely heard in the news. Pedophilia is a sexual disorder that has the desire to have sex with children under the age of 13. In addition to having sex, other pedophiles are satisfied by watching child pornography which is spread on prohibited sites and joining sexual deviation groups to make video calls for sex. If they do not have direct sexual intercourse, the pedophile can satisfy his lust by interacting online with the victim in the form of erotic chat, sending pictures and videos, and audio that triggers sexual arousal. The object of pedophilia itself is minors and does not look at gender. The type of research used in this article is normative by utilizing laws, pedophilia books, and mass media in the form of articles. Research data shows that there is confusion in convicting a pedophile. This is because pedophilia can be classified as a mental disorder, psychological condition, or more towards sexual orientation. This deviant behavior will certainly damage the growth and development of a child as a future generation. This deviant behavior must be stopped. When the perpetrator begins to realize there is a sexual disorder, the perpetrator must consult his condition to a psychologist. If this deviant act damages and harms other people, the perpetrator must undergo severe sanctions. Because the perpetrator takes the opportunity to deceive and damage someone's morale.